Characterisation of Municipal Sewage Sludge as a Soil Improver and a Fertilizer Product - Pöykiö, Risto; Watkins, Gary; Dahl, Olli (Ecological Chemistry and Engineering S, 2019)
In this study, we have determined the main important physical and chemical properties of municipal sewage sludge and compared them to the requirements of the Finnish Fertilizer Product Act and Fertilizer Product Decree in order to assess the potential utilization of this by-product as a fertilizer. Except for Hg (1.4 mg/kg d.m.), the total concentrations of Cd, Cu, Ni, Pb, Zn, Cr and As in our sewage sludge were lower that the Finnish maximum permissible heavy metal concentrations for sewage sludge used as a fertilizer products. However, the sewage sludge may be utilized as a soil improver, a growing media or as a fertilizer product in landfill sites (e.g. surface structures) or in other closed industrial areas, because the above mentioned Finnish limit values are not applied at these sites. If the sewage sludge is to be utilized in these kinds of areas, an environmental permit may be needed. According to BCR-extraction, the lowest release potential (solubility) from the sample matrix was observed for sulphur (58.4 %) and the highest for Cd (100 %).